Proline-Catalyzed Diastereoselective Synthesis of Dihydroquinolinyl-Spirooxindole via Aza-Michael/Aldol Reaction - Enagandhula, Damodar; Adepu, Raju; Mainkar, Prathama S. (Synthesis, 2023)
An efficient diastereoselective synthesis of 1′,4′-dihydro-2′H-spiro[indoline-3,3′-quinolin]-2-one derivatives was achieved using catalytic amount of l-proline. The key reactions involved in the present tandem reaction are aza-Michael addition and aldol reaction. This atom economic reaction proceeded under mild conditions with a broad substrate scope and excellent diastereoselectivity in good to excellent yields.
Keywords: l-Proline; organocatalytic reaction; spirooxindole; aza-Michael addition; aldol condensation